Sosialisasi dan Pelatihan Pengolahan Sampah Organik Menjadi Eco-Enzyme - Delvi Yanti; Rahmi Awalina (Warta Pengabdian Andalas, 2021)
Waste that is not managed properly can cause the environment to become dirty and cause silting of the river which results in flooding. The amount of waste production is in line with the large number of residents, the higher the population growth rate, the higher and the rate of waste production. Waste management cannot only be done downstream, but also starts from upstream. Many programs have been carried out in waste management, one of which is a waste bank. The waste bank program encourages people to do sorting before depositing inorganic waste in the waste bank. Inorganic waste that can be recycled, such as plastic bottles used for mineral water, can be economically valuable by being put in a tube in a waste bank, while organic waste such as vegetable and fruit residues can be further processed into eco-enzymes. This activity aims to transfer knowledge and technology for processing organic waste into eco-enzymes, so that the community can participate in preserving the earth. The method of activities carried out was counseling and demonstration. This activity achieved the target in accordance with the objectives; this can be seen from the participation and enthusiasm of the community during the activity.